Affective States in the Process of Suicide: Experiences and Assumptions - Marcinkevičiūtė, Miglė; Gailienė, Danutė (Psichologija, 2024)
The emergence of affective states during the process of suicide is regarded as a serious indicator of suicide risk. This study aims to describe the experience of affective states characteristic of the suicide process and to raise assumptions about how these affective states develop over a person’s lifetime. A qualitative approach was employed in this study, with the objective of retrospectively exploring individuals’ life experiences through in-depth semistructured interviews. The research sample comprises 12 participants (4 men, 1 person with a nonbinary gender identity, and 7 women) who had attempted suicide no more than one year prior to the study and were receiving treatment at the Vilnius City Mental Health Centre at the time of data collection. Data were analysed using phenomenological interpretive analysis to identify recurring experiential patterns. The analysis revealed nine main experiential themes: some life difficulties experienced during the suicide process were not perceived as related to suicidality; repeated traumatic events provided a foundation for the formation of deep feelings of deficiency; a compensatory mechanism emerged to fill these feelings of deficiency; exhaustion developed from the effort to maintain this compensatory mechanism; the main trigger directly challenged the compensatory mechanism; an affective state followed the experience of the primary trigger; during the affective state, dissociation may help isolate psychological pain; suicidal thoughts during the affective state are experienced as arising automatically; and suicide is perceived as a means to end suffering. The findings of the study indicate that individuals’ narratives reveal a pattern of the formation of affective states characteristic of the suicide process. Through reflection, individuals are able to intuitively distinguish significant, distressing life events from those irrelevant to the suicide process and reconsider their experiences. This ability is a valuable resource for both intervention and postvention efforts.